2011
DOI: 10.1615/critrevimmunol.v31.i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Immune Function of Tenascin-C

Abstract: Our immune system is designed to protect us from danger. Upon pathogen invasion and tissue injury, activation of both innate and adaptive immunity enables us to combat infection and to repair tissue damage. Tenascin-C is a large, extracellular matrix glycoprotein that has a very tightly controlled pattern of expression. Little or no tenascin-C is expressed in most healthy adult tissues; however, it is rapidly and transiently induced at sites of tissue injury and infection. Persistent tenascin-C expression is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
106
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 0 publications
0
106
0
Order By: Relevance
“…92 Altogether these observations raise the question whether we can gain insight into potential consequences of abundantly expressed tenascin-C in irradiated tissue by understanding the role of tenascin-C in these other pathological contexts. Some of these aspects had been addressed in this issue by Giblin and Midwood and by Udalova et al 93 Tenascin-C and radiation induced inflammation Radiotherapy induces TGFb and thus could play an important role in irradiation associated inflammation. 94 In early stages TGFb may play a role in suppression of malignancy but at later stages may promote tumor progression.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%
“…92 Altogether these observations raise the question whether we can gain insight into potential consequences of abundantly expressed tenascin-C in irradiated tissue by understanding the role of tenascin-C in these other pathological contexts. Some of these aspects had been addressed in this issue by Giblin and Midwood and by Udalova et al 93 Tenascin-C and radiation induced inflammation Radiotherapy induces TGFb and thus could play an important role in irradiation associated inflammation. 94 In early stages TGFb may play a role in suppression of malignancy but at later stages may promote tumor progression.…”
Section: Induction Of Tenascin-c Upon Radiotherapymentioning
confidence: 99%
“…The tenascin-C gene (TNC) is a large intron rich gene, which in humans spans 97.68 kb of DNA on the antisense strand of chromosome 9, at locus 9q32-34/9q33.1 19,20 and of which only »7.9% is protein coding (reviewed in 21 ). The first partial gene sequence derived for chicken tenascin-C identified several transcripts of various lengths prompting the speculation that the transcript is alternatively spliced.…”
Section: Cloning the Tnc Genementioning
confidence: 99%
“…23 Transcriptional regulators of tenascin-C expression Expression of tenascin-C is regulated in a stimulus specific manner in humans, mice, rats and chickens; the promoter elements of which are well conserved up to around 250 bp upstream of the transcription start site (TSS), including a TATA box located 21 nucleotides downstream of the TSS. 24 Regulation of the tenascin-C promoter is influenced by many transcription factors ( Table 2)(reviewed in 21 ). These data illustrate how tenascin-C transcription may be induced or repressed in response to different subsets of stimuli including pathogen-associated molecular patterns (PAMPs), cytokines, reactive oxygen species, growth factors and mechanical stress.…”
Section: Cloning the Tnc Genementioning
confidence: 99%
“…Only low levels of TnC can be detected in normal adult tissue, but higher levels have been reported in the areas of cancer development, cardiovascular disease, or where wounds are healing. In vitro studies have shown that a range of factors implicated in cardiovascular disease appear to be able to stimulate TnC synthesis from fibroblasts (7,8). These factors include cytokines, growth factors, hypoxia, mechanical and oxidative stress, acidosis, angiotensin II, and hemodynamic forces (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that a range of factors implicated in cardiovascular disease appear to be able to stimulate TnC synthesis from fibroblasts (7,8). These factors include cytokines, growth factors, hypoxia, mechanical and oxidative stress, acidosis, angiotensin II, and hemodynamic forces (7,8). Streptococcus pyogenes throat infection triggers an inflammatory reaction that involves several proinflammatory cytokines, such as tumor necrosis factor-α (TNFα), IL-1, and IL-6 (5).…”
Section: Introductionmentioning
confidence: 99%